Plio-Quaternary deformation pattern along the Algerian margin: insights from multibeam bathymetry and seismic reflection profiles (Maradja 1 and Samra cruises) - Strzerzynski, P.; Domzig, A.; Yelles, K.; Cattaneo, A.; Deverchere, J.; Babonneau, N.; Mercier de Lepinay, B.; Capron, A.; Boudiaf, A.; Bracene, R. (TRABAJOS DE GEOLOGÍA, 2010)
Offshore Algeria, multichannel bathymetry and seismic reflection profiles provide evidencefor tectonic activity during the Pliocene and the Quaternary. Between Cherchell and Dellys (Algiersregion), we show that the evolution of the structural pattern along strike is controlled by inheritedstructures. On the basis of relative timing offshore and absolute timing onshore, we propose that theinitiation of the shortening of the Algerian margin starts at ~3Ma in direct relationship with a changeof the direction of movement between the African and European plates.